Thermal Regulation in Thin Vascular Systems: A Sensitivity Analysis (Communications in Computational Physics, 2024)
One of the ways natural and synthetic systems regulate temperature is viacirculating fluids through vasculatures embedded within their bodies. Because of theflexibility and availability of proven fabrication techniques, vascular-based thermalregulation is attractive for thin microvascular systems. Although preliminary designsand experiments demonstrate the feasibility of thermal modulation by pushing fluidthrough embedded micro-vasculatures, one has yet to optimize the performance before translating the concept into real-world applications. It will be beneficial to knowhow two vital design variables—host material’s thermal conductivity and fluid’s heatcapacity rate—affect a thermal regulation system’s performance, quantified in terms ofthe mean surface temperature. This paper fills the remarked inadequacy by performing adjoint-based sensitivity analysis and unravels a surprising non-monotonic trend.Increasing thermal conductivity can either increase or decrease the mean surface temperature; the increase happens if countercurrent heat exchange—transfer of heat fromone segment of the vasculature to another—is significant. In contrast, increasing theheat capacity rate will invariably lower the mean surface temperature, for which weprovide mathematical proof. The reported results (a) dispose of some misunderstandings in the literature, especially on the effect of the host material’s thermal conductivity, (b) reveal the role of countercurrent heat exchange in altering the effects of designvariables, and (c) guide designers to realize efficient microvascular active-cooling systems. The analysis and findings will advance the field of thermal regulation both ontheoretical and practical fronts.